2018
DOI: 10.1109/tits.2017.2750401
|View full text |Cite
|
Sign up to set email alerts
|

Synergies of Electric Urban Transport Systems and Distributed Energy Resources in Smart Cities

Abstract: Transport systems and buildings are among the bigger energy users inside cities. Abundant research has been developed about these systems (facilities and transport). However, synergies among them are commonly overlooked, not taking advantage of the possible benefits of their joint coordination and management. This paper presents a linear programming model to find the optimal operation and planning of distributed energy resources (DER) in a residential district, while considering electric private and public tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
22
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(23 citation statements)
references
References 17 publications
0
22
0
1
Order By: Relevance
“…The regenerative braking energy from metro trains in urban transportation systems can be used as an RER for powering other metro trains or even EVs. The study [27] has conducted a case study for this use of the regenerative braking energy of metro trains for the metro system of Madrid, Spain. The goal of this study was to evaluate the effectiveness of using RERs for EVs and metro trains.…”
Section: B Integration Of Rers In Rail Transport Systemmentioning
confidence: 99%
See 2 more Smart Citations
“…The regenerative braking energy from metro trains in urban transportation systems can be used as an RER for powering other metro trains or even EVs. The study [27] has conducted a case study for this use of the regenerative braking energy of metro trains for the metro system of Madrid, Spain. The goal of this study was to evaluate the effectiveness of using RERs for EVs and metro trains.…”
Section: B Integration Of Rers In Rail Transport Systemmentioning
confidence: 99%
“…The goal of this study was to evaluate the effectiveness of using RERs for EVs and metro trains. The study [27] concluded that the use of regenerative braking energy from metro train can reduce the costs for operating the metro system while using EVs as energy storage devices.…”
Section: B Integration Of Rers In Rail Transport Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…There are multiple research, government and industry initiatives which aim to make electric vehicles more sustainable and scalable. For example, proposals for Smart Grids (SGs) integration with EVs [10,12,14,15] by supporting two way energy flows and two way communication flows (e.g. V2G) is a promising way forward.…”
Section: Introductionmentioning
confidence: 99%
“…Uno de los principales factores energéticos en las ciudades, con un consumo superior al 40 %, es el transporte según el Instituto para la Diversificación y Ahorro de la Energía (IDAE). Esto señala a los vehículos como una fuente potencial de mejora en el sector energético de las ciudades (Calvillo et al, 2018). Mediante la tecnología vehículo a red (V2G), los vehículos eléctricos pueden contribuir a equilibrar los intercambios energéticos en microrredes (Renato et al, 2015).…”
unclassified